2014
DOI: 10.1097/mib.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis

Abstract: The FC test is a reliable marker for assessing IBD disease activity and may have greater ability to evaluate disease activity in UC than CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(90 citation statements)
references
References 30 publications
4
76
0
5
Order By: Relevance
“…A meta-analysis of FC measurements as assessment of IBD activity pooled 13 studies (1471 patients) and found that 66% of the patients had disease activity when FC was measured. 8 This difference in prevalence could explain the lower PPV and higher NPV found in our study. A more generalizable measure is the LR+ or LR2, which can be used to determine whether a test result (i.e., a given FC concentration) usefully changes the probability of a specific condition, for example, a relapse in patients with IBD.…”
Section: The Calprosmart Test and Its Predecessormentioning
confidence: 80%
See 3 more Smart Citations
“…A meta-analysis of FC measurements as assessment of IBD activity pooled 13 studies (1471 patients) and found that 66% of the patients had disease activity when FC was measured. 8 This difference in prevalence could explain the lower PPV and higher NPV found in our study. A more generalizable measure is the LR+ or LR2, which can be used to determine whether a test result (i.e., a given FC concentration) usefully changes the probability of a specific condition, for example, a relapse in patients with IBD.…”
Section: The Calprosmart Test and Its Predecessormentioning
confidence: 80%
“…The cutoff of 200 mg/g was per protocol and based on studies showing high-positive predictive values (PPV) for relapse around 150 to 300 mg/g while ruling out symptoms arising from irritable bowel syndrome. 5,8,21,22 Statistics Chi square tests or Mann-Whitney Wilcoxon tests were used for comparison of patients' characteristics. To assess sample-to-sample reproducibility of the CalproSmart test, 42 different fecal samples (21 from patients with CD and 21 from patients with UC) were tested 3 times on 3 different LFDs using the same extraction, and the interassay coefficient of variation (CV) was calculated.…”
Section: The Calprosmart Test Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Faecal specimens do not necessarily reflect the nature of the mucosa-adherent bacteria, 18 nor the degree of inflammation. 19 While the use of faecal calprotectin measurements is useful in the setting of screening for gastrointestinal inflammation, 20 it is not as accurate as endoscopic or histological assessment in patients with IBD, especially those with small bowel inflammation. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%